Ampliação do repertório funcional de portadores de deficiência física. - Souza, Daniela Maria Xavier de (2003)
Several studies have shown that disabled people attending is done in a insufficient way in our country, being it an important social problem. Besides that, disabled ones also run into difficulties because of prejudice and lack of social support, what limits their roles as productive beings in the society. Besides some important achievements have been made in these days, as a better conscious of the need of participation of the disabled people in society, and some changes in the laws, still concrete changes are not enough to reach the needs of the disabled, showing that the law changes are also not enough to change reality. In this way, efforts are needed in order to guarantee that the disabled one has conditions to exert his/her citizenship, having access to the resources available. This work focus on delineating and evaluating effectiveness of a program to increase functional repertoire of disabled people, by means of the amplification or redirection of his/her participation on daily life activities. Six persons with disabilities acquired during their lives were selected to take part in the research, being between 24 and 31 years-old, users of a physiotherapy clinic, entailed to a public university. A one being its own control delineation was used to evaluate the effects of the program. The proceedings of the base line were done with every participant for at least three weeks, to evaluate the activities made by them routinely, and to make a characterization of their psychological well being; the evaluations of the progress were done during the whole work. The intervention program consisted in working with the disabled person and his/her family in the establishment of priorities in short and long terms for the involvement of the participant in relevant activities, including capacitating activities and the search of effective enrollment in such activities. The establishment of goals constituted an important product for the participants, but the results related to the amplification in participation and involvement in activities showed the need of alternatives for some participants. For those who showed themselves not very active, the program directed for extending activities and social contact sources, having this goal fully achieved in some cases, achieved for a temporary period in others, and not achieved in some cases. Normally active participants directed the establishment of goals for adjusting their daily activities to their physical condition. Results of the program showed incipient, but the research work resulted important consequences, such as raising questions targeting life quality and social insertion of disabled people.